Dynamic Propagation of Initially Chirped Airy Pulses in a Quintic Nonlinear Fiber - Yu Yu; Yating Zhang; Xiaoxian Song; Haiting Zhang; Mingxuan Cao; Yongli Che; Heng Zhang; Jianquan Yao (IEEE Photonics Journal)
We numerically simulate dynamic propagation of finite-energy Airy pulses in anomalous and normal regions of optical fiber and analyze the effects of quintic nonlinearity and initial chirp on evolution properties. Numerical results show that the effects of quintic nonlinearity on finite-energy Airy pulse imposed by initial chirp in two regions are entirely different. In anomalous dispersion region, soliton pulses shed from all finite-energy Airy pulses whether they are chirped or not, and quintic nonlinearity has profound effects on the propagation dynamics of the soliton pulse. However, in normal dispersion region, none soliton pulses are generated from Airy pulses. Depending on the peak intensity varying with the propagation distance, differing from the cases in the abnormal dispersion region, the effect of quintic nonlinearity has a slight impact on the evolution of Airy pulse.